Mead acid inhibits retinol-induced irritant contact dermatitis via peroxisome proliferator-activated receptor alpha - Saika, Azusa; Tiwari, Prabha; Nagatake, Takahiro; Node, Eri; Hosomi, Koji; Honda, Tetsuya; Kabashima, Kenji; Kunisawa, Jun (Frontiers in Molecular Biosciences, 2023)
Retinol is widely used in topical skincare products to ameliorate skin aging and treat acne and wrinkles; however, retinol and its derivatives occasionally have adverse side effects, including the induction of irritant contact dermatitis. Previously, we reported that mead acid (5,8,11-eicosatrienoic acid), an oleic acid metabolite, ameliorated skin inflammation in dinitrofluorobenzene-induced allergic contact hypersensitivity by inhibiting neutrophil infiltration and leukotriene B4 production by neutrophils. Here, we showed that mead acid also suppresses retinol-induced irritant contact dermatitis. In a murine model, we revealed that mead acid inhibited keratinocyte abnormalities such as keratinocyte hyperproliferation. Consistently, mead acid inhibited p38 MAPK (mitogen-activated protein kinase) phosphorylation, which is an essential signaling pathway in the keratinocyte hyperplasia induced by retinol. These inhibitory effects of mead acid were associated with the prevention of both keratinocyte hyperproliferation and the gene expression of neutrophil chemoattractants, including Cxcl1 and Cxcl2, and they were mediated by a PPAR (peroxisome proliferator-activated receptor)-α pathway. Our findings identified the anti-inflammatory effects of mead acid, the use of which can be expected to minimize the risk of adverse side effects associated with topical retinoid application.